(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The research investigates the durability properties of concrete produced with metakaolin (MTK) as partial replacement of cement. Cement was partially replaced by metakaolin at 5% to 30% at an interval of 5%. Physical properties of materials were tested. A 100 x 100 x 100mm cube was used for density, compressive strength, water absorption and abrasion resistant test, while, 100mm x 200mm cylinder was used for split tensile strength, at a mix ratio of 1:2:4 with 0.5 w/c ratio, and cured at 7, 14, 28, 56 and 90 days under different curing conditions. Result shows that the density of concrete increase as the curing ages of concrete increases. The highest compressive strength of concrete at 28days was at 0% control which achieved 28.2 N/mm2 and 27.6 N/mm2, while, 10% has the highest strength of 32.1 N/mm2 and 31.1 N/mm2 at 90 days for concrete cured in H2SO4 and MgSO4 respectively. 10% MTK concrete has reduce absorption capacity of 11.34, 11.17% and 6.57% in H2O, H2SO4 and MgSO4 respectively, as compared to that of control concrete, and has improve resistance to abrasion in aggressive environment. Chemicals significantly affect the strength of concrete. MgSO4 is more deleterious to concrete than H2SO4. In conclusion, metakaolin is a suitable pozzolana for use in the production of concrete, at lower volume of replacement will enhance the reduction of cement usage in concretes, thereby reducing the production cost and environmental pollution from exploration and production of cement. 10% MTK is the optimum percentage in concrete, therefore,...